2021
DOI: 10.3390/ijerph182211943
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Connection Analysis of Information Sharing and Investment Performance in the Venture Capital Network Community

Abstract: In order to explore the internal connection between information sharing and investment performance in the venture capital network community, this study took environmental-governance start-ups as the research object and used the 2009–2020 environmental-social enterprise start-up venture capital investment events as a data sample. The successful exit rate of the venture capital portfolio and the successful listing rate of investment ventures were used as the measurement criteria. Combined with regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Based on technological innovation, talent capital, and innovative talent management theories, this study proposes a hypothesis of the relationship between talent capital, R&D investment, and enterprise innovation performance. In order to verify these hypotheses, by the statistical data of new ventures that are now available, statistical analysis methods are used to analyze the hypotheses to prove the validity empirically ( Feng et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on technological innovation, talent capital, and innovative talent management theories, this study proposes a hypothesis of the relationship between talent capital, R&D investment, and enterprise innovation performance. In order to verify these hypotheses, by the statistical data of new ventures that are now available, statistical analysis methods are used to analyze the hypotheses to prove the validity empirically ( Feng et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier research, Cook observed four musical elements, i.e., rhythm, musicality, cultural shock, and relevance. The author proved that music was a crucial emotion regulation strategy and highlighted the potential use of music as a tool for emotion regulation ( Cook et al, 2019 ; Feng et al, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…On this basis, combined with the cooperative game theory and international green SCF models, a cooperative non-cooperative game model of commercial banks and core enterprises in green SCF is constructed. Analyzing the individual and overall benefits of the two in cooperation and non-cooperation shows the necessity of collaboration between commercial banks and core enterprises further to promote the implementation of the green SCF strategy and also points out the way forward for further development of green SCF in China (Zhang et al, 2022;Feng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%